Effects of Erdosteine Administration in Serum C-Reactive Protein Level in Stable Chronic Obstructive Pulmonary Disease Patients - Eko Budiono; Neneng Ratnasari; Lina Tjandra (Acta Interna The Journal of Internal Medicine, 2017)
Background.  Systemic inflammation contributes to the development of intrapulmonary and extra pulmonary disorders, and as an independent risk factor for exacerbation of chronic obstructive pulmonary disease (COPD) has proven. The use of corticosteroids as anti-inflammatory agents has limitation for their undesirable side effects and different efficacy among the patients. Erdosteine, a mucolytic agent widely used in COPD, has been proven to be able to inhibit several mediators such as reactive oxygen species (ROS) and eicosanoids, which are involved in oxidative stress and inflammation.Objective. This study aimed to discover the effects of erdosteine administration in serum C - reactive protein (CRP) level in stable COPD patients.Methods. The research was a randomized controlled trial, which compared add-on therapy used erdosteine 300 mg bid versus placebo, for 10 days, combined with COPD standard treatments. The patients was recruited at RSKP Respira Yogyakarta outpatient clinics. Diagnoses were confirmed used spirometry based on GOLD criteria. Evaluation of CRP levels was hold before treatment and on the eleventh day, used highly sensitive quantitative immunometric assay.Result. Thirty-eight legible COPD patients recruited and randomly assigned to either erdosteine group or placebo group. One patient in erdosteine group was drop out because of exacerbation and one patient from each group were lost to follow up. There are 35 subjects (97.1% men, age range 40-77 years, median FEV1 0.83 (0.50-10.08) L, hs-CRP 0.84 (0.18-18) mg/L) who completed the study, 19 subjects in erdosteine and 16 subjects in placebo group. Baseline characteristics were similar between two groups. There were no significant decreases in median hs-CRP level in erdosteine vs. placebo group at day 11 (-0.10 (-16.16-+4.31) vs. 0.005 (-11.7-+11.03) mg/L; p 0.275). In COPD GOLD 3 sub-population, hs-CRP serum level decline was greater in erdosteine group compared to placebo (-0.56 (-16.16-+0.44) vs. 0.11 (-11.7- +11.03) mg/L;  p 0.03) this might be related to greater oxidative stress in severe COPD that makes antioxidative effects of erdosteine reduce CRP more significantly in severe COPD.Conclusion. Effects of erdosteine supplements, 300 mg bid for 10 days, could decrease hs-CRP level in erdosteine insignificantly compared to placebo. Keywords: table COPD, C-reactive protein, erdosteine, FEV1, GOLD